Faktor – faktor yang mempengaruhi lamanya mencari pekerjaan di Desa Betung Bedarah Timur Kecamatan Tebo Ilir - Jumairi Jumairi; Yulmardi Junaidi; Junaidi Junaidi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The purpose of the study was to analyze and study the factors influencing job search in Betung Bedarah Timur Village, Tebo Ilir District. The analytical method used in this research is descriptive qualitative analysis and quantitative analysis. Data processing is performed using multiple linear regression. Based on the results of the study using statistics, that is to see the comparison of the silmultan test which are all variables of age, education, and gender together against the duration of unemployment in Betung Bedarah Timur Village, Tebo Ilir District, Tebo Regency. If partially tested the variables that have participation and education have a significant effect on the duration of unemployment in Betung Bedarah Timur Village, Tebo Ilir Subdistrict, Tebo Regency, while the income and gender variables are not significant on the duration of unemployment in Betung Bedarah Timur Subdistrict, Tebo Ilir Subdistrict, Tebo Regency.